Complex macromolecular architectures : synthesis, characterization, and self-assembly - Hadjichristidis, Nikos, 1943-; Wiley InterScience (Online service) (Hoboken, N.J. : Wiley, 2011)
"Despite very active research activities in the field of CMA, there lacks a simple-to-read book for researchers and students interested in these new developments. In each chapter, current progress in the area of the synthesis, characterization, and self-assemblies of well-defined complex macromolecular architectures is reviewed by each contributor with relevant emphasis on their research topics. The architectural polymers include bio-conjugated hybrid polymers with poly( -amino acid)s and gluco-polymers, star-branched and dendrimer-like hyperbranched polymers, cyclic polymers, dendrigraft polymers, rod-coil and helix-coil block copolymers are introduced chapter by chapter in the book. In particular, the book also emphasizes the topic of synthetic breakthroughs by living/controlled polymerization since 2000. Newly developed concepts and procedures, such as "Click" chemistry, chain walking, polyhomologation and ADMET are also highlighted. Furthermore, renowned authors contribute on such special topics as helical polyisocyanates, metallopolymers, stereospecific polymers, hydrogen-bonded supramolecular polymers, conjugated polymers, and polyrotaxanes, which have attracted considerable interest as novel polymer materials with potential future applications. In addition, recent advances in reactive blending achieved with well-defined end-functionalized polymers is discussed from an industrial point of view. Moreover, topics on polymer-based nanotechnologies, including self-assembled architectures and suprastructures, nano-structured materials and devices, nanofabrication, surface nanostructures, and their AFM imaging analysis of hetero-phased polymers are included"--
"In particular, the book also emphasizes the topic of synthetic breakthroughs by living/controlled polymerization since 2000"--
Front Matter -- Synthesis. Cyclic and Multicyclic Topological Polymers / Takuya Yamamoto, Yasuyuki Tezuka -- Ultrarapid Approaches to Mild Macromolecular Conjugation / Andrew J Inglis, Christopher Barner-Kowollik -- Synthesis and Self-Assembly of Hydrogen-Bonded Supramolecular Polymers / Wolfgang H Binder, Claudia Enders, Florian Herbst, Katharina Hackethal -- Recent Synthetic Developments in Miktoarm Star Polymers with More than Three Different Arms / Akira Hirao, Mayumi Hayashi, Tomoya Higashihara, Nikos Hadjichristidis -- Precise Synthesis of Dendrimer-Like Star-Branched Polymers, a New Class of Well-Defined Hyperbranched Polymers / Hee-Soo Yoo, Akira Hirao -- Arborescent Polymers with a Mesoscopic Scale / Toufic Nabil Aridi, Mario Gauthier -- Hyperbranched Glyco-Conjugated Polymers / Toshifumi Satoh, Toyoji Kakuchi -- Highly Branched Functional Polymer Architectures by Click-Chemistry Strategies / Mieke Lammens, Filip Du Prez -- Living Alkene Polymerization for Polyolefin Architectures / Amelia M Anderson-Wile, Joseph B Edson, Geoffrey W Coates -- Precision Polyolefins / Erik B Berda, Kenneth B Wagener -- Polyhomologation: The Living Polymerization of Ylides / Jun Luo, Kenneth J Shea -- Phenylenevinylene Homopolymers and Block Copolymers via Ring-Opening Metathesis Polymerization / Chin-Yang Yu, Michael L Turner -- Block Copolymers Containing Rod Segments / Tomoya Higashihara, Mitsuru Ueda -- Synthesis of Well-Defined Poly(meth)acrylamides with Varied Stereoregularity by Living Anionic Polymerization / Takashi Ishizone -- Complex Macromolecular / Hermis Iatrou, Marinos Pitsikalis, Georgios Sakellariou, Nikos Hadjichristidis -- Characterization and Self-Assembly. Self-Assembly and Applications of Polyferrocenylsilane Block Copolymers / George R Whittell, Jessica Gwyther, David A Rider, Ian Manners -- Functional Polymeric Nanostructures Prepared by Self-Assembly and Beyond / Rachel K O'Reilly -- Morphologies of Block and Star-Branched Polymers with Three Components / Hirokazu Hasegawa -- Morphologies and Photophysical Properties of Conjugated RodCoil Block Copolymers / Chi-Ching Kuo, Cheng-Liang Liu, Wen-Chang Chen -- Bulk Self-Assembly of Linear Hybrid Polypeptide-Based Diblock and Triblock Copolymers / Šbastien Lecommandoux -- AFM Study of Comb (Co)Polymers with Complex Chain Architecture / Michel Schappacher, Alain Deffieux -- Tunable Thermoresponsive Polymers by Molecular Design / Richard Hoogenboom -- Fluorine-Containing Block Copolymers: Synthesis and Application as a Template for Nanocellular and Porous Structures Using Supercritical Carbon Dioxide / Hideaki Yokoyama, Kenji Sugiyama -- Architectural Polymers, Nanostructures, and Hierarchical Structures from Block Copolymers / Ian Wyman, Guojun Liu -- Block Copolymer Nanostructured Thin Films for Advanced Patterning / Michelle A Chavis, Evan L Schwartz, Christopher K Ober -- Ring Polymers: Effective Isolation and Unique Properties / Haskell W Beckham -- Index.
Includes bibliographical references and index.
Print version record.
Keywords: Macromolecules; Polymerization; Macromolecules; Polymerization; Electronic books